Social capital and regional health governance in Saskatchewan, Canada - Veenstra, David Gerry (My University, 1998)
The relationship between social capital in a community and effective political governance by regional health boards in Canada was explored. A model was proposed that identified components of social capital such as trust, commitment and identity, associational and civic participation and collaborative problem-solving. These concepts were theoretically linked to effective governance--in particular to reflection of health needs, policy making and implementation, fiscal responsibility and the integration and coordination of services. The theoretical model was then tested empirically in Saskatchewan, Canada, where district health boards (DHBs) have been in operation since 1993. We found little evidence of a relationship between social capital in health districts and the performance of corresponding DHBs. Using a survey of randomly selected citizens from eight districts (n = 534) we explored relationships among the individual-level components of social capital delineated in the model. The behavioural components of the model--associational and civic participation and past experience collaborating to solve community problems--were significantly and positively related to one another. After controlling for socio-demographic characteristics we found that certain forms of trust, identity and commitment were positively and significantly related to these social capital behaviours.
Keywords: Sociology; Sociology